The influence of bid-ask spread and leverage on earnings management with good corporate governance as moderating variable - Putri, Yura Karlinda Wiasa; Sujana, I Ketut (International Research Journal of Management, IT & Social Sciences, 2018)
This research was intended for obtaining an empirical evidence regarding good corporate governance to moderate the influence of bid-ask spread and leverage on earnings management. Earnings management was measured by the three proxies of real earnings management. It was included cash flow operation, production cost, and discretionary expenses. Bid-ask spread was measured by ask and bid price of the companys shares in given period. Leverage was measured by the ratio of total debt and assets. A good corporate governance was measured by score Corporate Governance Perception Index (CGPI). The research population was a company listed on the Indonesia Stock Exchange in 2008-2015. The sampling method is used a purposive sampling. The samples analyzed was 56 samples. An analytical technique is used Moderated Regression Analysis (MRA). The result showed that a good corporate governance did not moderate the influence of bid-ask spread on earnings management. However, a good corporate governance weakens the influence of leverage on earnings management.